Bringing formative classroom assessment to schools and making it count. Issue 4 (19th August 2014) - Gordon, Edmund W.; McGill, Michael V.; Sands, Deanna Iceman; Kalinich, Kelley M.; Pellegrino, James W.; Chatterji, Madhabi
Abstract : Purpose: This article presents alternative views on the theory and practice of formative assessment, or assessment to support teaching and learning in classrooms, with the purpose of highlighting its value in education and informing discussions on educational assessment policy. Design/methodology/approach: The method employed is a "moderated policy discussion". The six invited commentaries on the theme represent perspectives of leading scholars and measurement experts juxtaposed against voices of prominent school district leaders from two education systems in the United States (U.S.). The discussion is moderated with introductory and concluding remarks from the guest-editor, and is excerpted from a recent blog published by Education Week. References and author biographies are presented at the end of the article. Findings: While current assessment policies in the U.S. push for greater accountability in schools by increasing large scale testing of students, the authors underscore the importance of formative assessment integrated with classroom teaching and learning. They define what formative classroom assessment means in theory and in practice, consider barriers to more widespread use of formative assessment practices, and address what educational policy-makers could do to facilitate a formative assessment "work culture" in schools. Originality/value: The commentators, representing scholar and practitioner perspectives, examine the problem in a multi-faceted manner and offer research-based, practical and policy solutions to the observed issues in formative assessment. Dialogue among key stakeholders, as presented here, is a key first step in enacting assessment reforms in the directions discussed.